2004
DOI: 10.5897/ajb2004.000-2106
|View full text |Cite
|
Sign up to set email alerts
|

The value of morpho-anatomical features in the systematics of Cucurbita L.

Abstract: Comparative studies on the morphology and anatomy of the three species of Cucurbita L. (C. moschata, C. maxima and C. pepo) in Nigeria were carried out. The morphological features of significance include variations in the number of tendrils, fruit size, shape, nature of fruit stalk, leaf shape and flower colour. Seed-coat anatomy revealed four distinct zones, which varied in thickness and tissue layers. Similarities were observed in the distribution, differentiation and number of layers of cells and tissues in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…The glabrous and reticulate seed outer integument surface, was previously described by Ajmal et al 21 The description of the sclerenchymatous tissue strata, observed in cross and transverse sections, matches other author's reports for Cucurbitaceae family. 17,22 The macroscopic features found for S. nigrescens, are similar to those described for other members of Solanum genus. 23 Microscopically, the presence of bicollateral bundles are typical for Species of the Solanum genus.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The glabrous and reticulate seed outer integument surface, was previously described by Ajmal et al 21 The description of the sclerenchymatous tissue strata, observed in cross and transverse sections, matches other author's reports for Cucurbitaceae family. 17,22 The macroscopic features found for S. nigrescens, are similar to those described for other members of Solanum genus. 23 Microscopically, the presence of bicollateral bundles are typical for Species of the Solanum genus.…”
Section: Discussionsupporting
confidence: 67%
“…The macroscopic characters find for C. argyrosperma seeds and aerial parts, are consist with those found in literature. 16 The microscopic characteristics of stem petiole and leaf correspond with descriptions of Agbagwa and Ndukwu, 17 for some species of cucurbita. The bicollateral vascular bundles are typical of Cucurbitaceae family.…”
Section: Discussionsupporting
confidence: 64%
“…The pistil consists of three carpels fused in one ovary with 3 short styles partially fused at their base, each of which ends with a bilobed stigma. Stigmas are large, fleshy or sunken, or lobulated, and slight modifications can be seen in the structure of the perianth regarding the staminate ones, mainly corresponding to differences in the size of one or some of its parts (Agbagwa and Ndukwu, 2004;Caracuel et al, 2012;OECD, 2016).…”
Section: Morphological Characteristics Of Selected Flower Parts Of Cu...mentioning
confidence: 99%
“…Male flowers are on pedunculate raceme with 6-10 flower heads or sometimes solitary with very long peduncles, more numerous and earlier than the female flower (Agbagwa, and Ndukwu, 2004;Vidal et al, 2010).…”
Section: Length and Width Of Petalsmentioning
confidence: 99%
“…In most studies fruit characters indicate high diversity and play a role in explaining affinity and distance between accessions and species. Ferriol et al (2003) and Ikechukwu et al (2004) used qualitative and quantitative characters of C. maxima accessions to study relationships between traits and genetic diversity and found variation in tendril number, fruit size and shape, nature of fruit stalk, leaf shape, and flower color, and the usefulness of their results will provide evidence for delimitation of species in the genus of these important vegetable species.…”
mentioning
confidence: 97%